Eksplorasi Efektivitas Asam Galat Sebagai Neuroprotektif dalam Menghambat Penyakit Alzheimer : Literatur Review - Ragil Parameswari Adji (Jurnal Cakrawala Akademika, 2025)
Alzheimer s disease is one of the diseases that continues to increase where there have been about 50 million cases in the world. Alzheimer's disease is a neurodegenerative disorder characterized by progressive cognitive decline and memory loss that often occurs in the elderly. Gallic acid is a type of phytochemical compound that is high in antioxidants and is considered to slow the progression of Alzheimer's disease because it can avoid or neutralize the damaging effects of free radicals. However, there are still few scientific articles that explain the effect of gallic acid on Alzheimer's disease so it needs to be reviewed further. This scientific article was prepared using the literature review method sourced from several journals searched through several databases such as Google Scholar, PubMed, and ScienceDirect. The purpose of preparing this scientific article is to find out more about the effect and mechanism of gallic acid treatment on Alzheimer's disease. The results show that gallic acid treatment with its antioxidant effects can significantly restore some of the symptoms caused by Alzheimer's disease.